Alternate protein sources as a partial substitute for fishmeal in nutritional formulations for shrimp (Litopenaeus vannamei) farming. (Orinoquia, 2023)
Recently, many researchers have carried out studies related to the nutrition of aquaculture species, in order to partially or totally replace the source of protein that is commonly used in nutritional formulations, a wide range of raw materials, both of vegetable and animal origin, have been evaluated, many of which present considerable potential for the supply of essential nutrients in aquaculture species, despite this, the use of any raw material represents different risks that must be mitigated in order to obtain safe, economically viable and sustainable food, for to maintain the sector. This document presents alternative sources as a partial substitute for fishmeal, for nutritional formulations in farmed shrimp feed Litopenaeus vannamei.
Keywords: substitution, alternate sources, essential nutrients, raw materials.